Characteristics of goals scored in open play at the 2017 and 2018 Australian national cerebral palsy football championship - Goh. A. M.; Drinkwater, E. J.; Harms, C. A.; Scanlan, M.; Newton, R. U.; Ma`ayah, F. (International Journal of Sports Science & Coaching, 2023)
Despite increasing popularity of cerebral palsy (CP) football (para football) worldwide, there are limited data available describing effective attacking strategies that lead to goals. The purpose of this research was to investigate the most frequent methods of ball repossession, distribution and movement patterns that successfully led to goals scored in open play of CP football. Video footage of all goals (n = 167) during the Australian National CP Football Championships in 2017 and 2018 were analysed using SportsCode software. Most goals (89.8%) were scored from open play, with the most effective mode of ball delivery identified as being direct play, of four or less passes, to create an opportunity to score. More goals were scored during the first half of games (54.9%), with a majority of goals (67.1%) scored from a region that encompasses the entire penalty area (Zone 1). The findings from the research conclude that tactically, coaches could capitalise on restarts by moving the ball quickly in four or less passes into the middle of the penalty area, to increase their chances of scoring goals in CP football.